DEPRESSIVE SYMPTOMS AFTER STOPPING SPOUSAL CAREGIVING - Perone, A (Innov Aging, 2018)
Few studies focus on the mental health of caregivers who stop providing care to their spouse. We know little about these caregivers. Building on Pearlin’s Stress Process Model, this study addresses depressive symptoms of primary spousal caregivers who stopped providing care at follow-up under three circumstances: (1) the care recipient (CR) continues to have functional problems; (2) the CR no longer has functional problems; and (3) the CR died. Using data from the Health and Retirement Study (2000–2014), we included 2,383 couples who were 50+ to identify the first instance of stopping spousal caregiving for ADL and/or IADL limitations over consecutive two-year periods. Results from OLS regressions (stratified by gender) indicate that both male and female former spousal caregivers whose CR died had significantly more depressive symptoms than those who stopped care when their spouse still had functional problems or no longer had such problems. While caregiver’s own baseline mental health and follow-up physical and mental health are associated with higher depressive symptoms for both genders, working for pay at follow-up is associated with lower depressive symptoms for both genders. For wife caregivers, those who were older and whose husband had more baseline number of ADLs had lower depressive symptoms, and those whose husband had a nursing home stay had higher depressive symptoms. For husband caregivers, those who provided longer weekly hours of care had lower depressive symptoms. Findings underscore the importance of targeting mental and physical health services to both husbands and wives after their spouse dies.